Two new sympatric Sarotherodon species (Pisces: Cichlidae) endemic to Lake Ejagham, Cameroon, west-central Africa, with comments on the Sarotherodon galilaeus species complex - Neumann, Dirk; Stiassny, Melanie L. J.; Schliewen, Ulrich K. (Zootaxa, 2011)
Morphometric differentiation among 25 populations of the widespread Sarotherodon galilaeus species complex is investigated, and two new species are described from Lake Ejagham, Cameroon in west-central Africa. Sarotherodon lamprechti sp. nov. is characterized by a prognathous lower jaw, scales over the pectoral fin-base restricted at maximum to the basal third, and an elongate ventral keel on the lower pharyngeal jaw. Sarotherodon knauerae sp. nov. is characterized by the possession of an inflated second pharyngobranchial element of the upper pharyngeal jaw, and small size at maturation. It is further differentiated from its sympatric congener in having a shorter anal fin (12.0–14.6 % SL vs. 14.1–15.7 % SL), larger eyes (24.0–31.2 % HL vs. 20.4– 29.2 % HL), higher total gill raker count (24–30 vs. 20–25), and a terminal mouth. Molecular evidence for a sister group relationship for these two sympatric species is corroborated by the shared possession of a reduced number of teeth on the second pharyngobranchial element of the upper pharyngeal jaw.